Digitalisasi Administrasi dan Peningkatan Kinerja Tata Kelola Kampung: Analisis Efektivitas Pelayanan, Transparansi, dan Partisipasi Masyarakat di Kampung Yuwanain - Muchsin, Muhamad (Jurnal Ilmiah Administrasi Publik, 2026)
The urgency of digital transformation in village administrations reflects the need to enhance public service efficiency, strengthen transparency in governance, and expand opportunities for community participation. This study examines the extent to which administrative digitalization improves service performance, information access, and citizen engagement, while also assessing the readiness of village officials in Yuwanain Village. Using a correlational survey design, the research involved residents and officials selected through stratified random sampling. Data obtained through questionnaires were analyzed using descriptive statistics, regression, and correlation techniques to determine relationships among variables. The findings show digitalization is positively associated with better service delivery, transparency, and higher community participation. Additionally, officials' competence emerges as a key factor in reinforcing the outcomes of digital transformation. These results offer practical insights for local governments in shaping targeted digitalization policies and provide theoretical contributions to the development of digital governance models at the village level.